Use of Expressive in Interpersonal Communication of Students who Need Counseling Services at SMP Negeri 56 Palembang - Eno Leriani; Evia Darmawani; Arizona Arizona (Edumaspul: Jurnal Pendidikan, 2024)
Language is the ability to express desires and needs through communication. The function of language is basically a statement of thoughts or feelings as a tool for communication, carried out in writing or orally according to the opportunity to express language with its relative scientific power. Not all students at SMP Negeri 56, especially in interpersonal communication, are able to express their feelings using expressive language. It was identified that 1 to 3 people in each class like to make noise based on expressive language, causing negative impacts such as bullying among their friends. This research aims to determine the use of expressive language in interpersonal communication of students who need counseling services. The research uses quantitative descriptive methods. The research sample consisted of 62 students from classes VII A and VII B. Data collection techniques used questionnaires and documentation. Data analysis uses the percentage formula (F/N X 100%). The results of this study indicate that the frequency of each use of expressive language in interpersonal communication is in the very low category which requires counseling services. Expressive language was 30 students with a percentage of 48% and interpersonal communication was 33 students with a percentage of 53% of the total number of respondents. Based on the data that has been processed and analyzed, it can be concluded that the use of expressive language in students' interpersonal communication is in the very low category so that counseling services are needed so that the implementation of this communication can run well, of course the language factor and the way it is expressed need to be taken into account. Keywords: Expressive Language, Interpersonal Communication ABSTRAKBahasa yakni kemampuan untuk mengungkapkan keinginan dan kebutuhan melalui komunikasi. Fungsi bahasa pada dasarnya merupakan pernyataan pikiran atau perasaan sebagai alat untuk komunikasi, dilakukan secara tertulis maupun secara lisan sesuai dengan kesempatan untuk mengekspresikan bahasa dengan daya relatifnya secara ilmiah. Tidak semua siswa di SMP Negeri 56 khususnya dalam komunikasi interpersonal mampu menyatakannya perasaan dengan bahasa ekspresif, teridentifikasi 1 sampai 3orang disetiap kelas suka ribut dilatar belakangi bahasa ekspresif sehingga menimbulkan dampak negatif seperti pembullyan sesama teman. Penelitian ini bertujuan untuk mengetahui penggunaan bahasa ekspresif dalam komunikasi interpersonal siswa yang membutuhkan pelayanan konseling. Penelitian menggunakan metode deskriptif kuantitatif. Sampel penelitian berjumlah 62 siswa dari kelas VII A dan VII B. Teknik pengumpulan data menggunakan angket dan dokumentasi. Analisis data menggunakan rumus presentase (F/N X 100%). Hasil penelitian ini menunjukkan bahwa frekuensi masing-masing dari penggunaan bahasa ekspresif berkomunikasi interpersonal pada kategori sangat rendah yang membutuhkan pelayanan konseling. Bahasa ekspresif sebanyak 30 siswa dengan persentase 48% dan komunikasi interpersonal sebanyak 33 siswa dengan persentase 53% dari jumlah responden. Berdasarkan data yang telah diolah dan dianalisis maka dapat disimpulkan bahwa penggunaan bahasa ekspresif dalam komunikasi interpersonal siswa masuk dalam kategori sangat rendah sehingga diperlukan pelayanan konseling supaya penerapan komunikasi tersebut dapat berjalan dengan baik tentu dari faktor bahasa dan cara pengekspresifnya perlu diperhatikan. Kata Kunci : Bahasa Ekspresif, Komunikasi Interpersonal